Desenvolvimento econômico e satisfação com a democracia: uma análise da América Latina - Roberta Carnelos Resende; Sara de Sousa Fernandes Epitácio (Ciências Sociais Unisinos)
The main goal of this work is to find out in which way the satisfaction with democracy can be associated with the level of economic development of the Latin American countries (1997-2009). As specific goals, we seek to analyze how Latin Americans assess the demo- cratic regime of their countries, whether there are considerable differences in evaluation at different times, whether the variations of expressions of satisfaction with democracy by individuals are correlated to economic variables, a nd, finally, whether it is possible to assure that a particular socioeconomic context influences the level of satisfaction with democracy. The data relating to the “satisfaction with democracy” were taken from the database of the Latinobarometro and the socio-economic data were collected from the World Bank. It was concluded that the social and economic situation of a country seems to influence, in a way, the individual utterances on the satisfaction with democracy.